Studies on the Response of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) to Multicolour Light System - Jinham, A. Premjith; Bhami, L. Charlet (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) commonly known as rust red flour beetle was a universal pest of stored produce with an extensive feeding diversity. The management of T. castaneum in field conditions was through fumigation and spraying of suitable insecticides. Even though many plant products were found effective against pests in invitro conditions, they could not be mixed with the stored produce for fear of losing the table quality. Physical forces seemed to be good alternatives to chemical treatment as far as stored grain pests were concerned. The use of gamma and UV radiations, microwaves and ultrasonic sound waves against T. castaneum and other stored grain pests had been tried by many authors. The objectives of this study were to check the adult beetles and final instar grubs of T. castaneum to different colours of light and it showedpreference for clear tungsten (white) light, while they were averse to red coloured light. This trend was explicit even after the entrainment of beetles to red colour light for further generations. Based on these results it could be presumed that T. castaneum adults preferred to move away from red coloured light. By changing the colour of bright light to dark lighting in warehouses, it could be possible to manage T. castaneum in small measure. Total eradication of stored product pests like T. castaneum was at least possibility and the selection of a proper management system could help to solve the stored produce pest problem to a greater magnitude.